E Analisis kepuasan mahasiswa terhadap pelayanan akademik Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta (Confirmatory Factor Analysis (CFA)): Analisis kepuasan mahasiswa terhadap pelayanan akademik Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta (Confirmatory Factor Analysis (CFA)) - Eko Ngabdul Shodikin Sogimin (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2021)
Service quality is a major concern in the management of higher education institutions. This is because the quality of higher education can be measured by the quality of service to students. In addition, the government also emphasizes to improve public services, one of which is administrative and academic services in educational institutions. The purpose of this study was to determine the factors that dominate student satisfaction. The population of this study were students at STIT Madani Yogyakarta with a total sample of 95 students. This analysis uses Confirmatory Factor Analysis (CFA). The dominant factor in the construct of student satisfaction is assurance and the weakest factor is reliability. The indicator that dominates the assurance dimension is the clarity of information about administrative and academic service procedures. Speed and alertness are needed to improve the quality of administrative and academic services at STIT Madani Yogyakarta.